Pembelajaran Hablum Minal Alam dalam Meningkatkan Perilaku Peduli Lingkungan di Sekolah Alam MI Bukit Pelangi Karanganyar Pekalongan - Rani Rakhmawati (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study examines the implementation of Hablum Minal Alam (human-nature relationship) learning in fostering environmentally conscious behavior at MI Bukit Pelangi Nature School in Karanganyar, Pekalongan. Using a qualitative approach, this research explores how Islamic values are integrated into an environmentally-focused curriculum based on direct experience with nature. The findings show that MI Bukit Pelangi effectively implements a contextual learning approach through activities such as farming, ecosystem observation, eco-brick projects, and nature reflection sessions. The curriculum combines the national "Merdeka Curriculum" with local contextualization and experiential learning methods. The study reveals that nature-based Islamic education successfully nurtures ecological awareness and environmental behavior through six core values: environmental consciousness, resource management, cultivation activities, gratitude for nature, stewardship responsibility, and experiential learning. This educational model offers potential as a sustainable environmental education framework that integrates spiritual values with ecological responsibility.